Elevated success of multispecies bacterial invasions impacts community composition during ecological succession. (14th February 2018) - Rivett, Damian W.; Jones, Matt L.; Ramoneda, Josep; Mombrikotb, Shorok B.; Ransome, Emma; Bell, Thomas
Abstract: Successful microbial invasions are determined by a species' ability to occupy a niche in the new habitat whilst resisting competitive exclusion by the resident community. Despite the recognised importance of biotic factors in determining the invasiveness of microbial communities, the success and impact of multiple concurrent invaders on the resident community has not been examined. Simultaneous invasions might have synergistic effects, for example if resident species need to exhibit divergent phenotypes to compete with the invasive populations. We used three phylogenetically diverse bacterial species to invade two compositionally distinct communities in a controlled, naturalised in vitro system. By initiating the invader introductions at different stages of succession, we could disentangle the relative importance of resident community structure, invader diversity and time pre‐invasion. Our results indicate that multiple invaders increase overall invasion success, but do not alter the successional trajectory of the whole community.